PERAN SOSIAL, EKONOMI, DAN BUDAYA MASYARAKAT DALAM MENINGKATKAN KEAMANAN DI KABUPATEN NATUNA PRIVINSI KEPULAUAN RIAU - Chairil N. Siregar (Jurnal Sosioteknologi, 2010)
Natuna Regency is located in a strategic area. It is blessed with a set of potential natural resources that has not been managed appropriately including marine fishery resources with their quantity of more than one million tons per year. In addition, Natuna has sources of D-Alpha gas located 225 km at north of Natuna Island (IEEZ) with a total of reserves of 222 billion Cubic Feet (TCT) and 46 TCT of hydrocarbon that becomes one of the largest hydrocarbon producers in Asia. The indigenous communities of Natuna are Malays and newcomers. The existing social institutions in Natuna society are still firmly held or implemented by the community hereditarily. The economic activities of Natuna communities are fishing and gardening, while communities in the surrounding islands are fishing with a very simple lifestyle. Due to its remote location, the prices of goods and basic necessities become expensive. Natuna is rich of Malays culture, marine tourism, and tourist nature but community empowerment has not been programmed properly. Compared to other regions, education in Natuna is still far behind so that it is necessary to develope a polytechnic education. In term of security, the most prominent problems of Natuna are illegal mining, illegal logging, illegal fishing, illegal trading, trafficking, drugs and illegal shift of boundary lines.